Managing Effectiveness of Public Health Performance in Surabaya City, Indonesia - Andy fefta Wijaya; Priyo Budi Santoso; Agus Suryono; Tjahjanulin Domai (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
This paper studies about managing the effectiveness of public health performance in Surabaya City, Indonesia. The research method uses a qualitative approach through focus group discussion elaborated with secondary data of the health sector performance. This paper proves that vertical and horizontal balanced performance measurements in the health sector are essential. Vertical stable performance is in the context of a hierarchical performance of top-level performance and lower-level performance in the public institution. In contrast, a horizontal balanced performance is the arrangement of qualitative and quantitative performance indicators and targets